Tertiary Lymphoid Organs in Cancer Tissues - Hiraoka, Nobuyoshi; Ino, Yoshinori; Yamazaki-Itoh, Rie (Frontiers in Immunology, 2016)
Tertiary lymphoid organs (TLOs) are induced postnatally in non-lymphoid tissues such as those affected by chronic infections, autoimmune diseases and chronic allograft rejection, and also in cancer tissues. TLOs are thought to provide important lymphocytic functional environments for both cellular and humoral immunity, similar to lymph nodes or Peyer’s patches. TLOs have a structure similar to that of lymph nodes or Peyer’s patches, including T cell zones, B cell follicles, and high endothelial venules (HEV) without encapsulation. Here we review recent advances in our knowledge of TLOs in human solid cancers, including their location, structure, methods of evaluation, and clinicopathological impact. We also discuss the formation and/or maintenance of TLOs in cancer tissues in association with the tumor immune microenvironment, cancer invasion, and the tissue structure of the cancer stroma.